2010
DOI: 10.5194/cp-6-817-2010
|View full text |Cite
|
Sign up to set email alerts
|

Warm Nordic Seas delayed glacial inception in Scandinavia

Abstract: Abstract.We simulate the last glacial inception, 115 000 years ago, with a three dimensional thermomechanical ice sheet model of the Northern Hemisphere, forced by a comprehensive coupled climate model. High oceanic heat transport into the Nordic Seas prevents large scale ice growth over Scandinavia. Glacial inception in the region starts on the highest mountains in the south when sea surface temperatures in the Nordic Seas are reduced by at least 3 • C.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…For example, Kubatzki et al (2006), using a fully coupled climateice-sheet EMIC, showed that during the last glacial inception (≈ 113 kyr BP in their study) the growth of the Laurentide ice sheet could have been delayed by modulating the state of ocean and vegetation. In the same line, Born et al (2010) suggest that, during the last glacial inception (≈ 115 kyr BP), the growth of the Eurasian ice sheet was delayed by a persistent high oceanic heat transport towards the Northern Hemisphere high-latitude regions.…”
Section: F Colleoni Et Al: Investigating Mis 5 and Mis 7 Glacial Insupporting
confidence: 50%
See 2 more Smart Citations
“…For example, Kubatzki et al (2006), using a fully coupled climateice-sheet EMIC, showed that during the last glacial inception (≈ 113 kyr BP in their study) the growth of the Laurentide ice sheet could have been delayed by modulating the state of ocean and vegetation. In the same line, Born et al (2010) suggest that, during the last glacial inception (≈ 115 kyr BP), the growth of the Eurasian ice sheet was delayed by a persistent high oceanic heat transport towards the Northern Hemisphere high-latitude regions.…”
Section: F Colleoni Et Al: Investigating Mis 5 and Mis 7 Glacial Insupporting
confidence: 50%
“…In the recent work of Herrington and Poulsen (2012) about the last glacial inception (≈ 115 kyr BP) over North America, no explicit ice shelves are simulated, but their ISM allows for floating ice over areas where ocean depth does not exceed 750 m. The limitation of this method resides in the fact that it may partly limit the growth of ice over oceanic regions deeper than 750 meters and as a consequence may induce incorrect ice distribution and volume. It is worth noting that in our ISM, ice shelves are explicitly simulated but a melting rate of 2.45 m yr −1 is prescribed below the shelves for ocean depths larger than 450 m. Born et al (2010) focused on the entire Northern Hemisphere but no ice shelf dynamics was considered. They argued that given the low ice volume observed during the last inception, the treatment of the marine part was of minor importance.…”
Section: F Colleoni Et Al: Investigating Mis 5 and Mis 7 Glacial Inmentioning
confidence: 99%
See 1 more Smart Citation
“…1) around 4.5 Ma. The establishment of the cold EGC, as a potential response to changes in the ocean circulation through the Bering Strait, has been considered important for large-scale glaciation of Greenland because the EGC thermally isolates Greenland from the warm waters transported northward in the Norwegian Atlantic Current (NwAC) (Bohrmann et al, 1990;Sarnthein et al, 2009;De Schepper et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A polar azimuthal projection is used as a grid base. The lateral grid is identical to the one of SICOPOLIS (Greve, 1997;Born et al, 2010).…”
Section: Model Domainmentioning
confidence: 99%